Natural but threatening? (II) A systematic terrestrial ecotoxicity evaluation of biopolymers and modified natural polymers - Winter, Marie; Broll, Gabriele; Philipp, Bodo; Díaz, Cecilia; Schlich, Karsten (Environmental research, 2025)
Polymers can be found in various agrotechnical products. While synthetic polymers and modified natural polymers are subject to EC 2023/2055 regulation, biopolymers can be regarded as unregulated substituents. However, there is no comprehensive data-based evidence which proves environmental harmlessness of (modified) natural polymer exposure to the terrestrial ecosystem. In order to assess the ecotoxicity potential, we conducted a systematic study with the six economically relevant bio- and modified natural polymers alginate, chitosan, the cellulose fibres Jelucel® HM 200, xanthan, CMC and the modified starch Emwaxy® Jel 100. We hypothesised, that the selected polymers are not ecotoxic within the test concentration range of 10 to 1000 mg/kg. As an evaluation strategy for the ecotoxicity of polymers is missing in the European regulation, we considered different terrestrial faunistic levels within the agricultural landscape for testing. We investigated the ecotoxicity impact on soil micro-, meso- and macrofauna with the OECD TG 216, ISO 15685, ISO 20130, OECD TG 232, ISO 17512-1 and OECD TG 222. Bacterial and archaeal amoA gene abundance was additionally analysed to link functional to structural diversity. Adverse effects were predominantly found for microbial soil functions related to potential nitrification. Collembola and earthworm reproduction, as well as earthworm movement behaviour, were mostly not impaired. Overall, the results indicate that biopolymers and modified natural polymers do have concentration-dependent effects on soil-living organisms and ecotoxicity tests with focus on the terrestrial compartment should be considered in an exposure-related hazard assessment framework. [Display omitted] •Biopolymers and modified natural polymers were evaluated in a systematic approach.•Effects on various soil organisms and functions were observed.•Potential nitrification was overall the strongest affected soil function.•Collembola and earthworm reproducibility were mostly unaffected.•Terrestrial organisms should be relevant in an exposure-based hazard assessment.